Junior Highschool Library Automation System Solution and Implementation - Sulistyo, Eko; Bhakti, Muhammad Agni Catur; Nurprihatin, Filscha; Liman, Surya Danusaputro; Lestari, Tika Endah; Islam, Sri Susilawati; Mileniawati, Indah Riantantri; Djajasoepena, Rafie; Ilham, Oryzea Sativa; Effendy, Muhammad Ikhsan; Wandy, Wandy (Center for Research and Community Service of Sampoerna University, 2023)
A high school library is a crucial part of educational infrastructures. Textbooks, e-books, and other collections in a library need to be recorded for circulation and administrative support needs. To provide data for statistical analysis, users of the library must tracked and recorded. Several library activities can be supported by a library automation system (SLiMS). East Jakarta's SMP Negeri 174 Jakarta is a public junior high school with a library. This project to install and implement SLiMS along with configuring the local network and library server. As a result, the library's infrastructure has been properly set up to support the library management system. Data entry for books and library members is currently underway. A guestbook option has also been added, and it is now switching from a manual guestbook to an electronic one to in order to precisely record library visitors.